Changes in periodontal parameters of splinted versus non-splinted posterior teeth during ten years of supportive periodontal therapy - A retrospective evaluation - Sonnenschein, Sarah K.; Kilian, Samuel; Rütters, Maurice; Ciardo, Antonio; Kim, Ti-Sun (Clinical oral investigations, 2024)
To compare periodontal parameters of splinted posterior teeth versus control teeth over ten years of supportive periodontal therapy (SPT) and to assess the survival rate of splints.